Sovereign Rights Oveer Indonesian Natural Resources: An Archipelagic concept of Rational and Sustainable Resource Management - Kusumaatmadja, Mochtar (Indonesian Journal of International Law, 2007)
This article is discussing about the problems in environmental, ecology, and oceanography, and the potential of South China Sea and the seas surroundings for the development of marine research and also for the environmental in that area protection.